A Method for Cranial Nerve XI Silencing During Surgery of the Foramen Magnum Region: Technical Case Report. Issue 4 (18th May 2018) - Southwell, Derek G; Breshears, Jonathan D; Lyon, William R; McDermott, Michael W
Abstract: BACKGROUND AND IMPORTANCE: Skull base surgery involves the microdissection and intraoperative monitoring of cranial nerves, including cranial nerve XI (CN XI). Manipulation of CN XI can evoke brisk trapezius contraction, which in turn may disturb the surgical procedure and risk patient safety. Here we describe a method for temporarily silencing CN XI via direct intraoperative application of 1% lidocaine. CLINICAL PRESENTATION: A 41-yr-old woman presented with symptoms of elevated intracranial pressure and obstructive hydrocephalus secondary to a hemangioblastoma of the right cerebellar tonsil. A far-lateral suboccipital craniotomy was performed for resection of the lesion. During the initial stages of microdissection, vigorous trapezius contraction compromised the course of the operation. Following exposure of the cranial and cervical portions of CN XI, lidocaine was applied to the course of the exposed nerve. Within 3 min, trapezius electromyography demonstrated neuromuscular silencing, and further manipulation of CN XI did not cause shoulder movements. Approximately 30 min after lidocaine application, trapezius contractions returned, and lidocaine was again applied to re-silence CN XI. Gross total resection of the hemangioblastoma was performed during periods of CN XI inactivation, when trapezius contractions were absent. CONCLUSION: Direct application of lidocaine to CN XI temporarily silenced neuromuscular activity and prevented unwanted trapezius contraction during skull base microsurgery. This method improved operative safety and efficiency by significantly reducing patient movement due to the unavoidable manipulation of CN XI.